Implementasi Wisata Edukasi Ramah Anak di Taman Lalu Lintas Kota Bandung - Dwiyani, Adelia Revana; Indrianty, Septy; Asti Karini, Rieke Sri Rizki (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
Taman Lalu Lintas Ade Irma Suryani Nasution is one of the first traffic-themed educational attractions in Indonesia with the concept of a theme park. The purpose of making this park is to increase traffic safety awareness for young children. This research was conducted to find out the tourist attractions in the park, and the implementation of child-friendly aspects considering that the main target of this park is children aged 0-13 years. The research method used is qualitative. Data collection techniques are carried out by direct observation, documentation, and interviews. The results show that the tourist attraction in the park follows the concept of educational tourism which presents attractions and facilities regarding basic traffic that can be learned by visiting tourists by learning while playing. As well as the existence of child-friendly indicators that are applied to the implementation of educational tourism at Taman Lalu Lintas Ade Irma Suryani Nasution by looking at the factors of Safety, Health, Comfort, Flexibility, Security, and Aesthetics which can make tourists feel free to travel in Taman Lalu Lintas Ade Irma Suryani Nasution.